Penerapan Profil Pelajar Pancasila Di Tingkat Sekolah Dasar - Wasilatul Ibad (JIEES : Journal of Islamic Education at Elementary School, 2022)
Pancasila of students profile is part of the merdeka curriculum and national education purpuse which is a reference of educators to building character and competence of students. Pancasila of students profiles have six dimensions, namely: 1) faith, piety of God, and noble morality, 2) independence, 3) cooperation, 4) global diversity, 5) critical thinking, and 6) creative. This research was descriptive qualitative study. The subject of this study was elementary high school of Bator 2 and object of this study was describing Pancasila of students profile values was implemented by student's elementary high school of Bator 2  .Techniques of the data collection through observation, interviews, documentation and triangulation (combined). The research showed that values from Pancasila of students profile applied at elementary high school of Bator 2  included as like the birth of Prophet's Muhammad, student introducing of various ethnicities and regional languages, Scout Movement, self-directed study, literacy and numeracy and Project Based Learning.